2008
DOI: 10.1080/09500340802353694
|View full text |Cite
|
Sign up to set email alerts
|

Nondegenerate parametric down conversion in coherently prepared two-level atomic gas

Abstract: We describe the parametric down conversion process in a two-level atomic gas, where the atoms are in a superposition state of relevant energy levels. This superposition results in splitting of the phase matching condition into three different conditions. Another, more important, peculiarity of the system under discussion is the nonsaturability of amplification coefficients with increasing pump wave intensity, under 'sideband' generation conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…It is interesting that contribution of this additional term is of resonant nature and has no saturation in dependence on pump wave intensity Ω. It repeats recently obtained regularity for the parametric down conversion process [13]. This out of dipole approximation contribution appears attractive in far IR or longer wavelength ranges of radiation.…”
Section: Referencessupporting
confidence: 78%
“…It is interesting that contribution of this additional term is of resonant nature and has no saturation in dependence on pump wave intensity Ω. It repeats recently obtained regularity for the parametric down conversion process [13]. This out of dipole approximation contribution appears attractive in far IR or longer wavelength ranges of radiation.…”
Section: Referencessupporting
confidence: 78%
“…Later we will refer to this scheme as QS (quantum superposition) generator. Another interesting result based on superposition principle was discussed in [15]. We showed that the phase matching condition for the parametric down conversion process is split into three conditions (it reminds one of Mollow's splitting in the case of one-photon luminescence).…”
Section: Introductionmentioning
confidence: 94%
“…In general this process can be accompanied by pulse amplification. It may be interesting, in addition, that the gas refractive index in comparison with earlier known results contains out of dipole approximation terms of resonant nature which have no saturation in dependence on pump wave intensity [15].…”
Section: Introductionmentioning
confidence: 99%